Influencia del juego dramático utilizado por las maestras en el desarrollo de la creatividad de los niños de primer año de educación básica de los centros educativos particulares Los Sueños de Alfred y Peke Talentos de la ciudad de Quito. Periodo 2010 – 2011 - Tigse Herrera, Carmen Inés; Casagallo Diaz, Lorena Patricia (2014)
This thesis refers to: DRAMATIC INFLUENCE GAME USED BY TEACHERS IN DEVELOPING CREATIVE KIDS FIRST YEAR OF BASIC EDUCATION SCHOOLS SPECIAL "DREAMS OF ALFRED " Y " PEKE TALENT" OF THE CITY QUITO. PERIOD 2010-2011. I structure and development is in accordance with the applicable Rules of Academic System, National University of Loja. The following overall goal to raise awareness of the importance of teachers use the Dramatic Play, to develop creativity in children Freshman Basic Education Private Education Centers "Alfred's Dreams" and "Peke Talents" was formulated in Quito 2010-2011. The methods used were: Scientist, Description, Inductive, Deductive, Statistical Model, techniques and instruments were applied to teachers of children in the First Year of Basic Education Special Education Centers " Alfred's Dreams " Survey and " Peke talents", to determine the use of Dramatic Play in your daily work, the observation guide given to children First-Year Basic Education Private Education Centers " Dreams from Alfred "Y" Peke Talent, assessing development Creativity. In the analysis of the survey found that: 100% of the teachers surveyed said they use the Dramatic Play in your daily work, stimulating their creativity in children as they develop the theme of the game. This activity also combines spontaneity, improvisation and play action, in an advanced stage of joint exercises and systematic work. As for the results of the observation guide is found that: 81% of children are developing Creativity Highly Satisfactory, Satisfactory 13%, and 6% Unsatisfactory. Creativity is one of the essential principles in all teaching-learning process. Cultivating Creativity in children is accustom to having a thought, thoughtful, critical, analytical, distinguished by its originality.